2015
DOI: 10.1111/mec.13476
|View full text |Cite
|
Sign up to set email alerts
|

Detecting spatial genetic signatures of local adaptation in heterogeneous landscapes

Abstract: The spatial structure of the environment (e.g. the configuration of habitat patches) may play an important role in determining the strength of local adaptation. However, previous studies of habitat heterogeneity and local adaptation have largely been limited to simple landscapes, which poorly represent the multiscale habitat structure common in nature. Here, we use simulations to pursue two goals: (i) we explore how landscape heterogeneity, dispersal ability and selection affect the strength of local adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
304
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 223 publications
(311 citation statements)
references
References 84 publications
6
304
0
1
Order By: Relevance
“…The reasons for the popularity of GEA analyses are practical: They require no phenotypic data or prior genomic resources, do not require experimental approaches (such as reciprocal transplants) to demonstrate local adaptation, and are often more powerful than differentiation‐based outlier detection methods (De Mita et al., 2013; de Villemereuil, Frichot, Bazin, François, & Gaggiotti, 2014; Forester, Lasky, Wagner, & Urban, 2018; Lotterhos & Whitlock, 2015). In particular, participants considered how and why detection rates differed between univariate and multivariate GEAs, exploring the use of latent factor mixed models (Frichot, Schoville, Bouchard, & Francois, 2013) and redundancy analysis (Forester, Jones, Joost, Landguth, & Lasky, 2016; Lasky et al., 2012), respectively. Recent work has shown that RDA is an effective means of detecting adaptive processes that result in weak, multilocus molecular signatures (Forester et al., 2018), providing a powerful tool for investigating the genetic basis of local adaptation and informing management actions to conserve evolutionary potential (Flanagan et al., 2017; Harrisson et al., 2014; Hoffmann et al., 2015).…”
Section: Improving Downstream Computational Analysesmentioning
confidence: 99%
“…The reasons for the popularity of GEA analyses are practical: They require no phenotypic data or prior genomic resources, do not require experimental approaches (such as reciprocal transplants) to demonstrate local adaptation, and are often more powerful than differentiation‐based outlier detection methods (De Mita et al., 2013; de Villemereuil, Frichot, Bazin, François, & Gaggiotti, 2014; Forester, Lasky, Wagner, & Urban, 2018; Lotterhos & Whitlock, 2015). In particular, participants considered how and why detection rates differed between univariate and multivariate GEAs, exploring the use of latent factor mixed models (Frichot, Schoville, Bouchard, & Francois, 2013) and redundancy analysis (Forester, Jones, Joost, Landguth, & Lasky, 2016; Lasky et al., 2012), respectively. Recent work has shown that RDA is an effective means of detecting adaptive processes that result in weak, multilocus molecular signatures (Forester et al., 2018), providing a powerful tool for investigating the genetic basis of local adaptation and informing management actions to conserve evolutionary potential (Flanagan et al., 2017; Harrisson et al., 2014; Hoffmann et al., 2015).…”
Section: Improving Downstream Computational Analysesmentioning
confidence: 99%
“…Given that mitochondrial and nuclear genomes can have largely independent evolutionary histories (e.g., different introgression patterns and mutation load), knowledge of the demographic history of the study system is especially useful to interpret patterns of mitonuclear co-evolution (Bar-Yaacov et al, 2015; Morales et al, 2016a,b; Pereira et al, 2016; Sloan et al, 2016). Given that mitonuclear co-evolution is likely to respond to environmental variation (Burton et al, 2013), approaches to detecting selection that rely on gene-environment associations could be particularly useful to identify candidate loci under selection (Rellstab et al, 2015; Forester et al, 2016). …”
Section: Integrative Approaches For Studying Mitonuclear Co-evolutionmentioning
confidence: 99%
“…If environmental conditions favor one phenotype, then populations may diverge phenotypically and genetically through local adaptation (43). The spatial arrangement of suitable habitat in heterogeneous landscapes, such as mosaics or clines, can also promote geographically clustered phenotypic variation (44). For example, strawberry poison dart frogs are highly polymorphic, and genetic distances among populations are more strongly associated with phenotypic differences than with geographic distances, suggesting a role for local adaptation related to predation and aposematism (25).…”
Section: Evolutionary Mechanisms Linking Genetic and Phenotypic Divermentioning
confidence: 99%